Time of Arrival and Angle of Arrival Statistics for Distant Circular Scattering Model - Guo Limei; Nian Xiaohong (Universitas Ahmad Dahlan, 2012)
General scattering model is local scattering process assumed that the mobile station is located inside the scattering region, in order to study distant scattering model in suburban or hilly propagation environment, a geometrically based statistical distant circular scattering mode in macrocell environment was proposed, the closed-form expressions of the joint probability density function of the time of arrival /the angle of arrival, the marginal probability density function of the angle of arrival and the angle of departure, the marginal probability density function of the time of arrival were derived, this probability density function’s provided insight into the properties of the spatial distant scattering channel model.